2021
DOI: 10.7759/cureus.13726
|View full text |Cite
|
Sign up to set email alerts
|

Late Onset Atraumatic Ceramic Head Fracture of a Hybrid Ceramic Bearings Total Hip Arthroplasty

Abstract: Ceramic head fracture is a major complication of ceramic-on-ceramic (CoC) total hip arthroplasty (THA) and though new generation ceramics have lowered the rates, although it is still a great concern. We report a case of late onset (more than 10 years after surgery) ceramic head fracture of a hybrid ceramic bearings to emphasize on its unusual clinical manifestation. Furthermore, we highlight the late onset presentation and also the rarity of this complication with this particular hybrid ceramic bearings. A rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There are very few reported cases of late, atraumatic fracture of a ceramic femoral head. Papaioannou et al [ 1 ] reported on a 71-year-old female who was 11 years out from her index surgery. The implants were a third-generation 28-mm ceramic femoral head (alumina, Biolox Forte, CeramTec, Plochingen, Germany) with a fourth-generation ceramic liner (Biolox Delta, CeramTec, Plochingen, Germany).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are very few reported cases of late, atraumatic fracture of a ceramic femoral head. Papaioannou et al [ 1 ] reported on a 71-year-old female who was 11 years out from her index surgery. The implants were a third-generation 28-mm ceramic femoral head (alumina, Biolox Forte, CeramTec, Plochingen, Germany) with a fourth-generation ceramic liner (Biolox Delta, CeramTec, Plochingen, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…The implants were a third-generation 28-mm ceramic femoral head (alumina, Biolox Forte, CeramTec, Plochingen, Germany) with a fourth-generation ceramic liner (Biolox Delta, CeramTec, Plochingen, Germany). Her risk factors were stated to be increased activity level, obesity, 28-mm ceramic head, and alumina on alumina matrix composite articulation, which is thought to cause low-temperature degradation of the zirconium [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations